Pan-African review of cultural uses of carnivores - Vivienne L. Williams; Marine Drouilly; Peter G. R. Coals; Gareth M. Whittington-Jones (PLoS ONE, 2025)
The consumptive use of fauna, encompassing the extraction of skins and derivatives, undermines vulnerable species’ resilience to persistent offtake. Evidence of pervasive, Africa-wide hunting and trafficking of wildlife underscores the need to understand the drivers and extent of this utilisation and exploitation. Here, we investigated evidence for the cultural use of 33 African carnivore species (Felidae, Viverridae, Nandiniidae, terrestrial Mustelidae) across Africa, a hitherto under-explored consumptive use threat, by conducting a systematic mixed-methods review and analysis of incidence records from nearly 600 published accounts and 555 YouTube videos. Aims were to: (i) characterise the main types of documented cultural uses behind the extraction and trade of selected carnivore taxa and examine the Africa-wide occurrence and extent of these practices; (ii) identify regional and national nexuses of African trade and trafficking; and (iii) explore factors that may perpetuate utilisation of certain species and products. Results for 48 African countries show that traditional use is widespread, including for purposes like attire, zootherapy and bushmeat. The culturally endowed legacy of diverse traditions suggests that these mostly under-reported and unquantified customary practices exist on a spectrum of cultural importance, impact, and extirpation risk for species population decline. Most incidence records were of spotted carnivore skins worn by traditional leaders, healers and participants in thousands of annual cultural events. In particular, leopards serve as prominent symbols of power and are mostly sought after by higher-ranking individuals. Lions are widely used in the attire of royalty, healing practices, and are periodically killed due to human-wildlife conflict with their parts sometimes subsequently removed and used. While most incidence-based records linked larger felids to traditional use, the reporting and impact on smaller spotted carnivores should not be overlooked. Smaller species also hold intrinsic cultural value, including skins for regalia and serving as substitutes for declining larger spotted felids.